Effect Of Trading Volume Activity And Stock Return On Stock Split (Financial Sector 2017-2021 Period) - Handayani, Adinda Putri; Sundarta, M. Imam; Azis, Azolla Degita (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
The purpose of this study was to determine whether TVA and stock returns affect the stock split. The data collection technique in this study was an event study to analyze the hypothesis, namely on the 5th, 10th and 15th days before and after the company did a stock split. The test results of the effect of TVA (X1) on the stock split using the partial T test method showed results that had a significant effect, while the test results for the effect of stock returns (X2) on the stock split using the partial T test method showed insignificant results, namely there was no effect of return. stock before and after the stock split event and the test results The effect of TVA and stock returns on stock split using the simultaneous test method F shows the results of the magnitude of the influence of the TVA variable and stock returns on the stock split is 26%, then this shows TVA and stock returns have an effect on stock splits in financial sector companies listed on the Indonesia Stock Exchange for the 2017-2018 period.